Implementasi Sistem Pembayaran Digital QRIS dalam Meningkatkan Pelayanan Publik (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
Along with the rapid growth of digital media, various forms of digital transactions have also developed.1 This development has driven changes in the payment system in Indonesia, one of which is through the implementation of QRIS (Quick Response Code Indonesian Standard). Despite its increasingly widespread use, there are still few studies that systematically examine user perceptions and the effectiveness of QRIS in improving transaction efficiency and strengthening the digital financial system. The purpose of this study is to identify and comprehensively analyze the results of previous studies related to QRIS use through a Systematic Literature Review (SLR) approach. Data were collected from Google Scholar and Garuda using the keywords "QRIS use", "QRIS payment system", and "QRIS transaction tool". The results show that QRIS can improve the efficiency and convenience of digital transactions, both for consumers and businesses, and facilitate the integration of financial services in a single platform. This study also aims to analyze the use of QRIS in public services. Using a descriptive qualitative research method, research data was taken from the results of searches of reliable sources including official websites, academic literature, theses, and national scientific journals relevant to the research topic. Thus, this may indicate that the success of QRIS is influenced by effective socialization, public awareness of transaction security, and equitable access to technology. The implications of this research provide a useful literature map for policy development and further studies in the field of digital finance.